2022
DOI: 10.1186/s12964-021-00818-8
|View full text |Cite
|
Sign up to set email alerts
|

CPNE1 promotes non-small cell lung cancer progression by interacting with RACK1 via the MET signaling pathway

Abstract: Background Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and the most lethal tumour worldwide. Copine 1 (CPNE1) was identified as a novel oncogene in NSCLC in our previous study. However, its specific function and relative mechanisms remain poorly understood. Methods The biological role of CPNE1 and RACK1 in NSCLC was investigated using gene expression knockdown and overexpression, cell proliferation assays, clonogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…EGFR signaling play an important role in tumorigenesis and progression ( Tomas et al, 2014 ). Previous studies showed that CPNE1 is a critical factor in the tumorigenesis of lung cancer and that its mechanism involves the EGFR signaling pathway ( Tang et al, 2018a ; Wang et al, 2022 ). Therefore, we detected the effect of CPNE1 on the regulation of EGFR signaling pathway in ccRCC.…”
Section: Resultsmentioning
confidence: 99%
“…EGFR signaling play an important role in tumorigenesis and progression ( Tomas et al, 2014 ). Previous studies showed that CPNE1 is a critical factor in the tumorigenesis of lung cancer and that its mechanism involves the EGFR signaling pathway ( Tang et al, 2018a ; Wang et al, 2022 ). Therefore, we detected the effect of CPNE1 on the regulation of EGFR signaling pathway in ccRCC.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the results of enrichment analysis of DEGs between the MW and LW placentas in the present study. Furthermore, studies on model animals have confirmed that knockdown of RACK1 suppresses cell growth in cultured cells and homozygous knockout of RACK1 is lethal for the embryo [45][46][47]. A recent study on pigs has shown that the proliferation and invasion of trophoblast cells affect the formation and development of PFs [27].…”
Section: Discussionmentioning
confidence: 98%
“…[41] Luteolin is a flavonoid abundant in fruits and vegetables, study has proved that it can improve anti-tumor immunity in KRAS-mutant lung cancer, [42] and inhibit the migration and invasion of NSCLC through MAPK and PI3K/Akt pathways. [43] Kaempferol, a flavonoid from natural plant sources, has proved to be effective in anti-NSCLC, specifically in inducing apoptosis in NSCLC cells, [44] promoting autophagy in NSCLC cells, [45] increasing the sensitivity to radiotherapy, [46] and inhibiting migration of A549 cells. [47] The PI3K-AKT signaling pathway is a key signaling pathway that regulates the progression of metastasis, [48] cell proliferation, differentiation, and metabolism.…”
Section: Discussionmentioning
confidence: 99%